Pengaruh Budaya Organisasi dan Kepemimpinan Terhadap Loyalitas Dosen Dengan Mediasi Spiritualitas Kerja - I Gusti Suka Arnawa; I Made Darsana (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2021)
Background: The decline in tourist visits during the COVID-19 pandemic in Bali affected the income of tourism actors in the region. This condition is a concern for tourism higher education in Indonesia, including Bali. One of the efforts made in this era of the covid-19 pandemic is to carry out internal integration related to educators or lecturers. Objective: to examine and explain the relationship between organizational culture and leadership on lecturer loyalty by mediating work spirituality at the Denpasar International Business and Tourism Institute. Design: the design of this research is quantitative with primary data sources through questionnaires to 90 lecturers of the Denpasar Institute of Tourism and International Business. Results: organizational culture and leadership have a positive and significant effect on work spirituality, organizational culture, leadership and work spirituality of lecturers have a positive and significant effect on lecturer loyalty, work spirituality is able to mediate the relationship between organizational culture and lecturer loyalty, but work spirituality is not able to mediate the relationship between leadership with lecturer loyalty at the Denpasar Institute of Tourism and International Business.